A glimpse at the external evaluation of schools in Portugal - Guerreiro, Helder; Barata, Isabel; Duarte, Leonor (Avances en Supervisión Educativa, 2023)
This article presents the process of the external evaluation of schools in mainland Portugal, developed by the Portuguese Inspectorate of Education (IGEC). In the first part, the evolution of external evaluation models for schools in Portugal is explained, driven by a law that made self-evaluation as well as external evaluation of schools mandatory, in 2002. Starting in 2006, the external school evaluation program has already made it possible to evaluate all public schools in mainland Portugal twice, and the third evaluation cycle, which started in 2018, is currently underway. In a second part, the framework, methodology and working instruments that support the task of evaluating schools, carried out by teams that include inspectors and higher education professors and/or researchers. The current external evaluation framework is made up of four domains, which correspond to major areas of the school’s performance: Self-evaluation, Leadership and management, Provision of educational services and Results, each of them classified according to the defined evaluation scale. Finally, in the third part it is highlighted the importance of inclusion as a process that aims to respond to the diversity of needs of all students. It is a focus of analysis of the external evaluation, found in the principles, objectives, and indicators of the current framework. A selection of excerpts from school reports are presented, reflecting the multiplicity of educational responses that they put into practice to respond to the specific needs of their students.